How does cannabidiol (CBD) influence the acute effects of delta-9-tetrahydrocannabinol (THC) in humans? A systematic review. (December 2019) - Freeman, Abigail M.; Petrilli, Katherine; Lees, Rachel; Hindocha, Chandni; Mokrysz, Claire; Curran, H. Valerie; Saunders, Rob; Freeman, Tom P.
Highlights: First systematic review of how CBD influences the acute effects of THC in humans. Sixteen studies were identified, including a total of 466 participants. Heterogeneity in dose, route of administration and THC:CBD ratio. Risk of bias across within and across studies was typically low. CBD influenced the effects of THC in some but not all studies. The most common finding was that CBD reduced the acute effects of THC, however, results were mixed. CBD may reduce intense experiences of anxiety or psychosis-like effects of THC but this was not seen in all studies. CBD may blunt effects of THC on emotion and reward processing. CBD did not alter subjective intoxication or psychomotor effects of THC. CBD may influence the benefits and harms of cannabis. Abstract: The recent liberalisation of cannabis regulation has increased public and scientific debate about its potential benefits and risks. A key focus has been the extent to which cannabidiol (CBD) might influence the acute effects of delta-9-tetrahydrocannabinol (THC), but this has never been reviewed systematically. In this systematic review of how CBD influences the acute effects of THC we identified 16 studies involving 466 participants. Ten studies were judged at low risk of bias. The findings were mixed, although CBD was found to reduce the effects of THC in several studies. Some studies found that CBD reduced intense experiences of anxiety or psychosis-like effects of THC and blunted some of the impairments on emotion and reward processing. However, CBD did not consistently influence the effects of THC across all studies and outcomes. There was considerable heterogeneity in dose, route of administration and THC:CBD ratio across studies and no clear dose-response profile emerged. Although findings were mixed, this review suggests that CBD may interact with some acute effects of THC.